The impact of mental fatigue on the accuracy of penalty kicks in college soccer players - Liu, Q.; Huang, R.; Liu, Z.; Sun, C.; Qi, L.; Cicchella, A. (Sports, 2025)
Purpose: To investigate the impact of mental fatigue on the shooting accuracy and movement timing in the instep kick of Asian high-level soccer players.